Pengaruh Profitabilitas, Resiko Keuangan, Nilai Perusahaan, Struktur Kepemilikan dan Dividend Payout Ratio terhadap Perataan Laba - Pratama, Dika Fajar (Journal of Accounting and Investment, 2012)
This research aims to test empirically the effect of profitability, financial risk, firm value, ownership structure and dividend payout ratio to income smoothing. The sample in this research are 33 manufacture companies that have been listed on the Indonesia Stock Exchange in period of 2006 to 2009. Sample was obtained by purposive sampling method. Analysis tool uses regression analysis with logistic regression method. Â The results of analysis indicate that profitability, financial risk, firm value, public ownership and dividend payout ratio do not influence income smoothing in manufacture companies except managerial ownership.